Hyperoxidized Peroxiredoxin 2 Is a Possible Biomarker for the Diagnosis of Obstructive Sleep Apnea - Koike, Shin; Sudo, Haruka; Turudome, Satori; Ueyama, Masako; Tanaka, Yoshiaki; Kimura, Hiroshi; Ishida, Yo-Ichi; Ogasawara, Yuki (Antioxidants, 2022)
Peroxiredoxin (Prx) 2 in red blood cells (RBCs) reacts with various reactive oxygen species and changes to hyperoxidized Prx2 (Prx2-SO2/3). Therefore, Prx2 may serve as an indicator of oxidative stress in vivo. This study aimed to analyze Prx2-SO2/3 levels in clinical samples to examine whether the oxidation state of Prx2 in human RBCs reflects the pathological condition of oxidative stress diseases. We first focused on obstructive sleep apnea (OSA), a hypoxic stress-induced disease of the respiratory system, and investigated the levels of Prx2-SO2/3 accumulated in the RBCs of OSA patients. In measurements on a small number of OSA patients and healthy subjects, levels of Prx2-SO2/3 accumulation in patients with OSA were clearly increased compared to those in healthy subjects. Hence, we proceeded to validate these findings with more samples collected from patients with OSA. The results revealed significantly higher levels of erythrocytic Prx2-SO2/3 in patients with OSA than in healthy subjects, as well as a positive correlation between the severity of OSA and Prx2-SO2/3 levels in the RBCs. Moreover, we performed a chromatographic study to show the structural changes of Prx2 due to hyperoxidation. Our findings demonstrated that the Prx2-SO2/3 molecules in RBCs from patients with OSA were considerably more hydrophilic than the reduced form of Prx2. These results implicate Prx2-SO2/3 as a promising candidate biomarker for OSA.